Brand loyalty dissociation: How consumers navigate brand loyalty in the attention economy marketplace - Milos Ivanis (Marketing Review St.Gallen, 2025)
Marketing needs to be aware of the complex nature of consumers' brand loyalty in today's attention-scarce marketplace. As such an environment poses significant challenges for consumers, they manifest and navigate brand loyalty in unique ways. An exploration of digital forums and lived experiences illuminates these navigation processes from an emic perspective.
Keywords: 650